EXTRACTION OF CURCUMIN PIGMENT AND STUDY ITS EFFICIENCY IN DYEING OF SCOURED COTTON FABRIC AND AS ANTIBACTERIAL AGENT - Mohammed, Ali; Majeed, Majid; Jasim, Hiba (Iraqi Journal of Science, 2024)
Extraction of curcumin pigment as dyestuff and Antibacterial agent fromTumeric (Curcuma xanthorrhizia) tubers was studied .also, the Qualitative chemicaltests was done for determine active materials in crud turmeric extract.The curcumin pigment was isolated and partially scrubbed by using organicsolvents. Detection by HPLC and TLC proved the isolated pigment is Curcuminwith partial purity compared to the standard curcumin.The curcumin showed ahigh efficiency of dyeing for scoured cotton fabric atconcentration 25% of curcumin and active biological effect against Gram – positivepathogenic bacteria with large inhibition zones from 12mm to 33mm by using Agarwells diffusion method.The results proved ability of curcumin on dyeing of cotton cloth fabric andantibacterial activity against bathogenic bacteria